(untitled) (Annals of Medical Research, 2023)
Aim: To examine the relationship between spousal support and depression, anxiety, stress, and prenatal attachment in high-risk pregnant women. Materials and Methods: Data were collected from 375 high-risk pregnant women in their 2nd/3rd trimesters in November 2021-February 2022. An introductory information form, the Spouse Support Scale (SSS), the Depression, Anxiety, and Stress Scale (DASS-21), and the Prenatal Attachment Inventory (PAI) were used to collect data. Results: Median SSS score was 76 (29-81), median PAI score was 74 (31-84). Median anxiety scale score was 4 (0-21), depression scale score was 2 (0-21), and stress scales score was 3 (0-21). There was a positive significant relationship between spousal support and prenatal attachment, and a negative significant relationship between spousal support and anxiety, depression, and stress (p<0.001). Conclusion: Inadequate spousal support in high-risk pregnancies is a risk factor for prenatal attachment, anxiety, depression, and stress levels.